Endocrine Society of Australia position statement on male hypogonadism (part 2): treatment and therapeutic considerations. Issue 5 (5th September 2016) - Yeap, Bu B; Grossmann, Mathis; McLachlan, Robert I; Handelsman, David J; Wittert, Gary A; Conway, Ann J; Stuckey, Bronwyn GA; Lording, Douglas W; Allan, Carolyn A; Zajac, Jeffrey D; Burger, Henry G
Abstract: Introduction: Part 1 of this position statement dealt with the assessment of male hypogonadism, including the indications for testosterone therapy. This article, Part 2, focuses on treatment and therapeutic considerations for male hypogonadism and identifies key questions for future research. Main recommendations: Key points and recommendations are: Excess cardiovascular events have been reported in some but not all studies of older men without pathological hypogonadism who were given testosterone treatment. Additional studies are needed to clarify whether testosterone therapy influences cardiovascular risk. Testosterone is the native hormone that should be replaced in men being treated for pathological hypogonadism. Convenient and cost‐effective treatment modalities include depot intramuscular injection and transdermal administration (gel, cream or liquid formulations). Monitoring of testosterone therapy is recommended for efficacy and safety, focusing on ameliorating symptoms, restoring virilisation, avoiding polycythaemia and maintaining or improving bone mineral density. Treatment aims to relieve an individual's symptoms and signs of androgen deficiency by administering standard doses and maintaining circulating testosterone levels within the reference interval for eugonadal men. Evaluation for cardiovascular disease and prostate cancer risks should be undertaken as appropriate for eugonadal men of similar age. Nevertheless, when there is a reasonable possibility of substantive pre‐existing prostate disease, digital rectal examination and prostate‐specific antigen testing should be performed before commencing testosterone treatment. Changes in management as result of the position statement: Treatment aims to relieve symptoms and signs of androgen deficiency, using convenient and effective formulations of testosterone. Therapy should be monitored for efficacy and safety.